Comparison of Physical Fitness Component in Heavy Weight Training Exercises of Men and Women - Dr. Yashpal Singh Bhati; Dr. Jagdish Narayan Saini (International Journal on Orange Technologies, 2021)
In the world of exercise and fitness, a 12-week strength training program for men and women dominates the landscape. You might have seen them in fitness magazines, over the years. So, are they successful? Yes, they are. But we're going to tell you an important secret: it doesn't always take 12 weeks to do a weight loss strength training program for women or men. Not that you're going to be a seasoned vet in just 4 weeks, but if you can only get the starting month under your belt, you will easily cross the proverbial hump, where so many people struggle, and eventually give up, and lay the groundwork for a lifetime of strength and muscle gains. We have designed the best strength training program for men and women, respectively. It does not matter if you are looking for strength training for weight loss or a strength training program for beginners, the given workouts can be easily modified to meet the needs of everyone from beginners to professionals with specific goals in mind. Moreover, even if you have been absent from the gym for months, the following programs will get back up and on the track in a few weeks.